Variations in Soil Moisture at Coimbatore - Jayaraman, M V; Balasubramanian, C (Journal of Soil and Water Conservation, 2022)
Soil moisture forms one of the most important factors in successful crop production, especially under rain-fed conditions in semi-arid tracts. The soil depends mainly on rainfall for its moisture content. " The relation between water and a complex body like soil is one of the most complicated problems in soil physics. These complications multiply in the field where the conditions are daily changing and where the meteorological conditions, over which no control is possible, influence the movement of soil moisture to a very great extent.Apart from the external factors, the in- herent characteristics of the soil are so very widely varying from field to field and from year to year in the same field that any mathematical explanation will be far from satisfactory.  Anyhow, in the following note the variations of soil moisture at dif- ferent depths, recorded at Agricultural Meteorological Observatory, Coimbatore, have been studied statistically with reference to rainfall and iaaxirnum temperature recorded inside a Sievenson Screen. The situated at Cotton observatory Breeding station, Coimbatore, and then shifted to Field No. 61, Western Block, Central Faun, ill January 1951. In both the areas the soil kept undisturbed, as far as possible, and also kept free from weeds, so that there no loss to soil moisture by transpiraton. The analysis is only a preliminary study the variations of soil moisture as would occur in a normal un- cultivated ban-en field in order to indicate the availability of moisture at different depths below the soil surface.